Family caregivers’ perspective of caring for cancer patients during radiotherapy: a qualitative study - Dewi, Lingga Curnia; Pratiwi, Ika Nur; Nimah, Lailatun; Ramoo, Vimala (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the perspective of family caregivers of cancer patients undergoing radiotherapy. Method: The descriptive, qualitative study was conducted at the Indonesia Cancer Foundation, Surabaya, Indonesia, in July and August 2019, and comprised family caregivers of cancer patients undergoing radiotherapy. Data was collected using in-depth semi-structured interviews which were recorded, transcribed and analysed using conventional content analysis. Results: Of the 26 caregivers aged 24-65 years, 16(62%) were men, 19(73%) were married, and 14(56%) had close relationships with the patients. Among the patients, 4(15.4%) had breast cancer, 2(7.6%) had nasopharyngeal cancer and 20(77%) had cervical cancer. The themes identified were uncertainty, disintegration and burden. Conclusion: Caregivers of cancer patients tended to have both physical and emotional challenges. Keywords: Caregivers, Adaptation, Psychological, Neoplasms, Cancer, Radiotherapy.